An assessment of risk compensation and spillover behavioural adaptions associated with the use of vaccines in animal disease management. Issue 5 (29th January 2020) - Enticott, Gareth; Maye, Damian; Naylor, Rhiannon; Brunton, Lucy; Downs, Sara H.; Donnelly, Christl A.
Highlights: Vaccination of badgers may reduce the spread of bovine tuberculosis to cattle. The paper examines evidence of risk compensation and spillover behaviours amongst farmers. Increased risk taking by farmers is associated with vaccination. Risk compensation is linked to low self-efficacy amongst farmers. Lack of spillover behaviour is due to low cultural saliency of vaccination. Abstract: This paper analyses farmers' behavioural responses to Government attempts to reduce the risk of disease transmission from badgers to cattle through badger vaccination. Evidence for two opposing behavioural adaptions is examined in response to the vaccination of badgers to reduce the risk of transmission to farmed cattle. Risk compensation theory suggests that interventions that reduce risk, such as vaccination, are counterbalanced by negative behavioural adaptions. By contrast, the spillover effect suggests that interventions can prompt further positive behaviours. The paper uses data from a longitudinal mixed methods study of farmers' attitudes to badger vaccination to prevent the spread of bovine tuberculosis, their reports of biosecurity practices, and cattle movement data in 5 areas of England, one of which experienced badger vaccination. Analysis finds limited evidence of spillover behaviours following vaccination. Lack of spillover is attributed to farmers' beliefs in the effectiveness of biosecurity and the lack of similarity between badger vaccination and vaccination for other animal diseases. Risk compensation behaviours are associated with farmers' beliefs as to who should manage animal disease. Rather than farmers' belief in vaccine effectiveness, it is more likely that farmers' low sense of being able to do anything to prevent disease influences their apparent risk compensation behaviours. These findings address the gap in the literature relating to farmers' behavioural adaptions to vaccine use in the management of animal disease.